ESTRUTURA FAMILIAR E GRAVIDEZ NA ADOLESCÊNCIA: UM ENFOQUE SISTÊMICO - Ewerton, Mary Lúcia Adler (2010)
Qualitative study, aiming to address the relationship between family structure and adolescent pregnancy in a systemic approach. Assumes that the family structure operates in the conduct of its members in influencing their decisions. The research was conducted at the Center for Health Care of Adolescents (NASA), the Maternal and Child Unit, and initiated after the approval of the Ethics in Research HU-UFMA. The inclusion criterion was adopted family have a pregnant teenager, between 10 and 19 years in attendance at NASA, Maternal and Child Unit. Families with pregnant adolescents with mental changes, hearing or language, not the object of study. The sample followed the criteria proposed saturation field, having participated in the study were eight families. Data collection was conducted from September to November 2009, initially being held at NASA, as teenagers, and then, in homes with families. Triangulation was made of instruments: semi-structured interviews with adolescents, interviews with families, genogram families and field observation. The method used was content analysis, in the form of thematic analysis for data processing. Some results include: the family speech is greatly effective in how teenagers interact with the risk for becoming pregnant. The nature of the relationship between mothers and daughters present interactional agendas of the previous generation with regard to the topic of sexuality and teenage pregnancy. The subjects of this study point to the structural determinism of family interaction resulting in the choice of becoming pregnant or not pregnant. In most families there was a transgenerationality of teenage pregnancy. The story of mothers operates as a guide and as a context of justification of the behavior of adolescents. It should be emphasized in conclusion that the plot that underlies the behavioral responses of family members is linked in large part to family structure and history shared by its members, sufficient reason for early pregnancy is the subject of a systemic intervention from family stories as preventive procedure.